Geophysical and Sedimentological Assessment of Urban Impacts in a Lake Ontario Watershed and Lagoon: Frenchman's Bay, Pickering, Ontario - Eyles, N.; Doughty, M.; Boyce, J.; Meriano, M.; Fraser, P. (Geoscience Canada, 2003)
Summary Managing the environmental impacts of urbanization on watersheds is a major problem facing Canadian communities. Meeting this challenge requires that municipal planning departments have access to good quality environmental information allowing them to develop effective land use plans and remediation policies. Managing such problems demands an interdisciplinary approach involving a range of scientific disciplines including geology, geochemistry, sedimentology, hydrogeology, hydrology, geophysics and aquatic ecology. Geoscientists from the University of Toronto and McMaster University are working with the City of Pickering, Ontario on remediation of a Lake Ontario lagoon and urbanized watershed (Frenchman's Bay) experiencing large stormwater flows and enhanced sediment erosion and transportation. Throughout the watershed, the hydrological cycle has been dramatically changed as a result of 'hardening' byroads and buildings - greatly restricting infiltration and promoting surface runoff. The urban-impacted watershed empties into the shallow, semi-enclosed coastal lagoon of Frenchman's Bay -serving as a trap for fine-grained contaminated sediment. A wide range of geophysical techniques have been employed in Frenchman's Bay lagoon to determine the geology of the lagoon, physical characteristics of bottom sediments and the distribution of contaminated sediment on its floor.